New vaccine production platforms used in developing SARS-CoV-2 vaccine candidates. Issue 2 (8th January 2021) - Ura, Takehiro; Yamashita, Akio; Mizuki, Nobuhisa; Okuda, Kenji; Shimada, Masaru
Abstract: The threat of the current coronavirus disease pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is accelerating the development of potential vaccines. Candidate vaccines have been generated using existing technologies that have been applied for developing vaccines against other infectious diseases. Two new types of platforms, mRNA- and viral vector-based vaccines, have been gaining attention owing to the rapid advancement in their methodologies. In clinical trials, setting appropriate immunological endpoints plays a key role in evaluating the efficacy and safety of candidate vaccines. Updated information about immunological features from individuals who have or have not been exposed to SARS-CoV-2 continues to guide effective vaccine development strategies. This review highlights key strategies for generating candidate SARS-CoV-2 vaccines and considerations for vaccine development and clinical trials.